Implementasi Model Pembelajaran Contextual Teaching And Learning (CTL) untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPS Kelas 4 MI - Natasya Sylvia Dewi; Anjar Wati; Oman Farhurohman (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research delves into examining how the Contextual Teaching and Learning (CTL) model can be applied to enhance students' academic performance in Social Sciences (IPS) for fourth-grade students at Madrasah Ibtidaiyah (MI). This research centers on studying literature to examine how the CTL model connects academic content with students' everyday experiences. By enhancing students' critical and social thinking abilities, this study aims to offer insights to educators on how to incorporate successful teaching approaches in madrasas to enhance student academic performance.